OP II – 5 Impact of meteorological parameters on suicide rates: a case-crossover study in southern germany (1990–2006). (18th March 2018) - Hampel, Regina; Schneider, Alexandra; Ladwig, Karl-Heinz; Baumert, Jens; Lukaschek, Karoline; Peters, Annette; Breitner, Susanne
Abstract : Background/aim: Researchers worldwide have reported a seasonal pattern of suicides with peaks in spring and early summer; however, only a limited number of studies has evaluated whether meteorological variables may trigger suicides. We therefore aimed to investigate the association between short-term changes of meteorological variables and suicides in Bavaria, Germany, for the period 1990–2006. Methods: Daily suicide and meteorological data were available for four Bavarian cities and ten counties. Immediate, delayed and cumulative effects of air temperature, sunshine duration, cloud cover, relative humidity as well as precipitation on suicides were analysed using a confounder-adjusted time-stratified case-crossover approach. In further analysis, we explored potential effect modifications by specific weather conditions (air temperature <median value or ≥median value; relative humidity <median value or ≥median value), personal characteristics (age, sex), place of residents (city or county), and season. Effect modifications were analysed by including an interaction term (meteorological variable*modifier) as well as the main effects of these two variables in the models. Results: A 5°C increase in air temperature was associated with a 4.1% (95%-confidence interval: 0.97; 7.4%) and 5.1% (2.0; 8.4%) higher suicide risk on the same day and with a delay of one day, respectively. Further, the suicide risk was 6.2% (0.6; 12.2%) higher on days with low/medium cloud cover (0–6 oktas) compared to days with high cloud cover (7–8 oktas). Temperature effects with a lag of one day were more pronounced in individuals older than 65 years (9.9% (4.3; 15.8%)). While temperature was not associated with suicides in spring we found positive associations in summer, autumn, and winter. The effects of cloud cover were strongest in summer and autumn and on days with temperature above the median (>8.8°C). The other meteorological variables were not significantly associated with suicides. Conclusion: We found a higher risk for suicides in association with short-term increases in air temperature and on days with low to medium cloud cover. This may highlight time periods when people are more likely to commit suicide.